The critical moment of transition: Staying with and acting on newly gained self- and social awareness. Issue 3 (July 2018) - Svalgaard, Lotte
By providing a holding environment to acknowledge sensitivities and address emotions, leadership programs prove to be powerful spaces for increasing self- and social awareness. However, the challenge is for one to maintain the newly gained self- and social awareness after leaving the holding environment and entering a context characterized by activity and performance. This is a frequently debated challenge for both academics and providers of management learning. Yet, critical moments in this transition remain under-exposed and under-researched. The contribution of this article is a research study—within the context of an international MBA program—of MBA students applying their knowledge from a Leadership Stream in an international consultancy project. This article contributes to the theory and practice of management learning by providing a lens through which subjective experience of critical moments of transition can be understood. In addition it develops the notion of 'mindful avoidance', and points to a major and neglected space in the design of management education.